2019
DOI: 10.1111/jam.14283
|View full text |Cite
|
Sign up to set email alerts
|

Persistence ofPseudomonas fluorescensLBUM677 in the rhizosphere of corn gromwell (Buglossoides arvensis) under field conditions and its impact on seed oil and stearidonic acid bioaccumulation

Abstract: Aims The aim of this study was to evaluate the persistence of Pseudomonas fluorescens LBUM677 in the rhizosphere of Buglossoides arvensis under agricultural field conditions and determine if B. arvensis intraspecific genetic variations affect the capacity of LBUM677 to colonize its rhizosphere and increase seed oil and stearidonic acid (SDA) accumulation. Methods and Results Two field experiments were performed to: (i) study the persistence of various concentrations of LBUM677 inoculated in the rhizosphere of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…LBUM677 was able to establish itself in the rhizosphere of the three plant species under study at similar levels, indicating that none of the plants had a significant effect on LBUM677's colonization abilities. The levels observed for the three plant species were higher than those previously measured in B. arvensis plants; however, this could be due to the previous levels having been measured in field settings and not in a controlled environment, as in this study (Novinscak and Filion , ). The results obtained in this study on the influence of different plant species on the rhizocompetence of Pseudomonas spp.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…LBUM677 was able to establish itself in the rhizosphere of the three plant species under study at similar levels, indicating that none of the plants had a significant effect on LBUM677's colonization abilities. The levels observed for the three plant species were higher than those previously measured in B. arvensis plants; however, this could be due to the previous levels having been measured in field settings and not in a controlled environment, as in this study (Novinscak and Filion , ). The results obtained in this study on the influence of different plant species on the rhizocompetence of Pseudomonas spp.…”
Section: Discussioncontrasting
confidence: 80%
“…also have, but to a lesser extent, been studied for their ability to increase seed oil content as well as fatty acid composition of oilseed crops (Kumar et al ). Previous studies by our research group have shown that P. fluorescens LBUM677 was able to increase oil and SDA yield in B. arvensis plants grown under field conditions (Novinscak and Filion , ). In this study, P. fluorescens LBUM677 colonization resulted in a significant increase in oil yield for all three plant species under study but led to a general plant growth promotion in only two out of three species, B. napus and B. arvensis .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations